Clinical utility of ramucirumab in advanced gastric cancer - Chan, Matthew MK (Biologics, 2015)
Gastric cancer is currently the third most common cause of cancer deaths worldwide. Prognosis remains poor with most patients presenting with advanced or metastatic disease. A better understanding of angiogenesis has led to the investigation of drugs that inhibit the vascular endothelial growth factor (VEGF) pathway including anti-VEGF antibody therapy (eg, bevacizumab), inhibitors of angiogenic receptor tyrosine kinases (eg, sunitinib, sorafenib, apatinib, regorafenib), and inhibitors of vascular endothelial growth factor receptors (VEGFRs) (eg, ramucirumab). Ramucirumab, a VEGFR-2 inhibitor, is the first anti-angiogenic agent approved by the US Food and Drug Administration for use in the treatment of advanced gastric cancers. This review will focus on the clinical utility and potential use of ramucirumab in advanced gastric cancer.